Scotland in the age of two revolutions - Adams, Sharon; Goodare, Julian (Studies in early modern cultural, political and social history, 2014)
The seventeenth century was one of the most dramatic periods in Scotland's history, with two political revolutions, intense religious strife culminating in the beginnings of toleration, and the modernisation of the state and its infrastructure. This book focuses on the history that the Scots themselves made.